The idea of Europe : the clash of projections - Biti, Vladimir, 1952-; Leerssen, Joseph Th. (Joseph Theodoor), 1955-; Liska, Vivian, 1956- (European studies: an interdisciplinary series in European culture, history, and politics, 2021)
"Recent developments within and beyond Europe have variously challenged the very idea of Europe, calling it into question and demanding reconsideration of its underlying assumptions. The essays collected here reassess the contemporary position of a perceived "European" identity in the world, overshadowed as it is by the long antecedents and current crisis of triumphalist Eurocentrism. While Eurocentrism itself is still a potent mind-set, it is now increasingly challenged by intra-European crises and by the emergence of autonomously non-European perceptions of Europe. The perspectives assembled here come from the fields of political, cultural and literary history, contemporary history, social and political science and philosophy. Contributors are: Damir Arsenijević, Luiza Bialasiewicz, Vladimir Biti, Lucia Boldrini, Gerard Delanty, César Domínguez, Nikol Dziub, Rodolphe Gasché, Aage Hansen-Löve, Shigemi Inaga, Joep Leerssen, and Vivian Liska"--